Equality and Anti-discrimination: The Relationship between Government Goals and Finding Discrimination in Section 15 - Lawrence, Sonia (The Oxford Handbook of the Canadian Constitution, 2017)
This chapter considers the effect of section 1, the “justification” section of the Canadian Charter, on the doctrinal development of section 15, the equality section. It begins by describing the development of the section 15 substantive equality analysis, including the claim of a conceptually complete separation from the section 1 analysis of state justification. The chapter then identifies some features of section 15 which suggest that this separation is less than complete, including the existence of section 15(2), and anxieties over constraining government action. The chapter then turns to three post-2001 cases in which the Supreme Court of Canada found discrimination under the Charter but then held that discrimination was “justified” through section 1, and asks what these cases might reveal about the symbolic significance of a finding of discrimination and the Court’s struggle with institutional competence concerns in equality claims.